Case Report: Supercharged end-to-side anterior interosseous to ulnar motor nerve transfer for ulnar nerve neuropathy after cross pinning of pediatric supracondylar humerus fracture - Chen, Jian-Jiun; Yang, Chen-Yuan (Frontiers in Pediatrics, 2024)
Ulnar nerve neuropathy following pediatric supracondylar humerus fracture fixation with cross pinning poses challenges in management. Despite various treatment strategies, including conservative approaches and early intervention, achieving complete neural recovery remains elusive in some cases. This paper presents a novel approach utilizing supercharged end-to-side anterior interosseous nerve transfer for a 13-year-old patient who experienced persistent ulnar neuropathy after K-wire removal. The patient underwent neurolysis of the ulnar nerve followed by nerve transfer, resulting in significant improvement in function and strength. This case highlights the potential efficacy of combining neurolysis and supercharge techniques in pediatric ulnar neuropathy cases refractory to conservative treatment, offering a promising avenue for enhancing patient outcomes.